Improved interfacial property of carbon fiber composites with carbon nanotube and graphene oxide as multi-scale synergetic reinforcements. (October 2019) - Zhang, Tong; Cheng, Qiancun; Xu, Zhiming; Jiang, Bo; Wang, Caifeng; Huang, Yudong
Graphical abstract: Abstract: In the present research, carbon nanotubes (CNTs) and graphene oxide (GO) were used to enhance the composites interfacial properties synergistically by the strategy combining electrodeposition and chemical grafting. It was found that the interface between CF and matrix can be tuned by the binary addition of CNTs and GO. The interfacial shear strength (IFSS) of GO/CNTs synergistic reinforced composites based on this physical and chemical combination method via the "bridge" of Ag nanoparticles (NPs) exhibits 42.99% and 4.61% enhancement compared to that of achieved by electrophoretic deposition (physical method) and chemical grafting (chemical method), respectively. In addition, the IFSS has 69.68% and 19.54% improvement due to the synergistic effect of GO/CNTs compared to the untreated CF and GO single-reinforced CF composites. Therefore, it is a promising technique for developing multifunctional CF with the excellent interfacial performance.